EVALUATING THE EFFECTIVENESS OF INTERVENTIONS TO REDUCE MEDICATION ERRORS: A SYSTEMIC REVIEW (Journal of Pharmaceutical Negative Results, 2023)
According to “World Health Organization” (WHO), medicines involve the 2nd highest disbursement after staff costs in a country’s health care system. The statistics of worldwide spending on medicines showed that in 2010; whole spending on medicine was 887 billion U.S. dollar and it is estimated that until 2025 the pharmaceutical market will gain to around 1.8 trillion U.S. dollars. There are 2 essential components for ensure the quality use of medicines. The first is to institute standards of practice that define standard operating procedures and the second is to recognizes the positions or persons, working within the accepted limits of their roles, who are accountable for implementing each-step of the process. The organization of drug supply is organized around five primary functions of the Medicines Management cycle namely- selection, quantification,procurement, distribution, and use. Rational use of drugs involves choosing the right drug, at the right dose, for the right duration, and for the right indication in the right patient. Adverse event and adverse drug reactions (ADRs) are terms used to describe any undesirable effect of a medical treatment, including a drug, a medical device, or a procedure. ADRs are usually mild and reversible, but can also be severe or even life-threatening. By following best practices for prescribing medications, health care providers can ensure that their patients receive the best possible care. This includes educating patients about their medications and monitoring them closely for any potential side effects or adverse reactions.